Highly twisted bipolar emitter for efficient nondoped deep-blue electroluminescence. (May 2017) - Huang, Zhi; Wang, Bo; Zhang, Qing; Xiang, Songpo; Lv, Xialei; Ma, Lixiang; Yang, Bing; Gao, Yu; Wang, Lei
Abstract: Three novel bipolar deep-blue emitters, 1-(4-( tert -butyl)phenyl)-2-(4-(9, 9-diphenylacridin-10(9 H )-yl)phenyl)-1 H -phenanthro[9, 10- d ]imidazole (DPACTPI ), 1-(4-( tert -butyl)phenyl)-2-(4′-(9, 9-diphenylacridin-10(9 H )-yl)-[1, 1′-biphenyl]-4-yl)-1 H -phenanthro[9, 10- d ]imidazole (DPACPhTPI ) and 2-(4-(9, 9-diphenylacridin-10(9 H )-yl)phenyl)-1-(4-(trifluoromethyl)phenyl)-1 H -phenanthro[9, 10- d ]imidazole (DPACFPPI ), employing the donor 9, 9-diphenyl-9, 10-dihydroacridine (DPAC) and the acceptor, phenanthroimidazole, were designed and synthesized. The highly twisted conformations between DAPC and phenanthroimidazole in the molecules efficiently interrupt molecular π-conjugation and inhibit π-π intermolecular interactions, resulting in good thermal stability and efficient deep-blue emission. The three phenanthroimidazole derivatives in non-doped OLEDs exhibited deep-blue emission. In particular, DPACPhTPI -based nondoped device showed an excellent performance with maximum external quantum efficiency (EQE) of 3.50%, maximum current efficiency (CE) of 1.38 cd/A, maximum power efficiency (PE) of 1.40 lm/W and CIE coordinate of (0.156, 0.047), which is among the best results for OLEDs with a similar color. The high radiative exciton utilization could be resulted from hybridized local and charge transfer (HLCT). Graphical abstract: Highlights: Three new deep-blue emitters were designed and synthesized. The highly twisted conformation inhibits π-π intermolecular interactions and results in a large blueshift in solid state. Nondoped OLED based onDPACPhTPI achieves a maximum EQE of 3.50% with a CIE coordinate of (0.156, 0.047).